Respon Masyarakat Terhadap Inovasi Hidroponik Dan Strategi Implementasinya di Desa Deah Raya Kecamatan Syiah Kuala - Agussabti, Agussabti; Satriyo, Purwana (JURNAL PENGABDIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (JP3L), 2024)
The Proposed Gampong-Based Community Service (PKM-BGB) aims to empower the community in Deah Raya Makam Syiah Kuala Village, Banda Aceh through the implementation of a hydroponic system. The proposing team consisted of two lecturers and 5 students who collaborated with Keuchik Gampong Deah Raya to provide training and assistance in making hydroponic plants to improve community welfare. The approach methods offered include preparation, coordination, implementation and coaching stages. This proposal is a community empowerment program with a hydroponic system in Deah Raya Makam Syiah Kuala Village, Banda Aceh, involving lecturers and students from Syiah Kuala University. This activity is planned to take place from March to July 2024. Evaluation of program implementation is carried out once a month by checking the results of hydroponic plants. The service team has competence and experience in community service activities.